EU law and military industries : sovereignty and strategic autonomy in military procurement - Meershoek, Nathan (Routledge research in EU law., 2026)
"This book addresses how the EU can promote European strategic autonomy to overcome contemporary military challenges while respecting the sovereignty of its Member States. At a time of rising military expenditure and growing European military cooperation, the application of EU law to military procurement and EU defence spending are at the heart of debates on European integration. Shortages in equipment and dependency on US military industries in the context of Russia's invasion of Ukraine have highlighted the need for European strategic autonomy. The book considers both the regulation of military procurement and the increasing amount of EU funding instruments for military industries. Providing a comprehensive overview of the EU's involvement, the book critically evaluates the compatibility of this involvement with the geopolitical- and constitutional context in which they exist. Concluding with innovative recommendations for future-proof regulation of military procurement and the embedding of EU funding therein, the book will provide practical guidance to promote the evolution of European integration while preserving its constitutional foundations and values. The book will be of interest to researchers in the field of EU law and politics, military industries and public procurement law"-- Provided by publisher.